Sistem Proteksi Arus Bocor Menggunakan Earth Leakage Circuit Breaker Berbasis Arduino - Syukriyadin Syukriyadin (Universitas Syiah Kuala, 2016)
Touching a live part of electrical equipment either intentionally or unintentionally can cause an electric shock. The touch can occur directly or indirectly and results in the flow of electric current through the human body to the ground. This electric current is known as the leakage current and can have fatal effects on the human body such as burns, cramps, faint and death. This paper aims to design a prototype protection model of the earth leakage circuit breaker device based on Arduino (ELCBA) to protect the human body from the electrical hazards. The performance of the ELCBA is investigated by detecting the earth leakage current to the grounding system (TN). The prototype is designed and simulated by using Proteus software. Based on the response test carried out on the prototype, it can be concluded that the ELCBA can operate properly to disconnect the electric circuit if the leakage current is detected greater than or equal to 30 mA with a time delay of 15 ms and to reclose the circuit again after 5 minutes.